2010
DOI: 10.1007/s00430-010-0155-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin inhibits highly pathogenic H5N1 influenza A virus-induced pro-inflammatory cytokine and chemokine expression in human macrophages

Abstract: Hypercytokinaemia is thought to contribute to highly pathogenic H5N1 influenza A virus disease. Glycyrrhizin is known to exert immunomodulatory and anti-inflammatory effects and therefore a candidate drug for the control of H5N1-induced pro-inflammatory gene expression. Here, the effects of an approved parenteral glycyrrhizin preparation were investigated on H5N1 virus replication, H5N1-induced pro-inflammatory responses, and H5N1-induced apoptosis in human monocyte-derived macrophages. Glycyrrhizin 100 μg/ml,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 53 publications
2
61
0
Order By: Relevance
“…This could mean that the high but delayed pro-inflammatory cytokine (IL-1b and IL-6) and IFN-g response was too late to clear the virus infection in chickens. In other studies it was shown that high expression of IL-6 (Michaelis et al, 2010;Hayashi et al, 2011) and IFN-a, IFN-b, IL-15, and IL-18 mRNA in the lung of HPAI H5N1-infected chickens was accompanied by high levels of viral titres (median egg infectious dose) (Suzuki et al, 2009 Karpala et al (2011a), the highly elevated IFN-g response in the lung of HPAI-infected chickens after 1.5 d.p.i. is an indication of an active Th1 immune response.…”
Section: Discussionmentioning
confidence: 87%
“…This could mean that the high but delayed pro-inflammatory cytokine (IL-1b and IL-6) and IFN-g response was too late to clear the virus infection in chickens. In other studies it was shown that high expression of IL-6 (Michaelis et al, 2010;Hayashi et al, 2011) and IFN-a, IFN-b, IL-15, and IL-18 mRNA in the lung of HPAI H5N1-infected chickens was accompanied by high levels of viral titres (median egg infectious dose) (Suzuki et al, 2009 Karpala et al (2011a), the highly elevated IFN-g response in the lung of HPAI-infected chickens after 1.5 d.p.i. is an indication of an active Th1 immune response.…”
Section: Discussionmentioning
confidence: 87%
“…This observation was confirmed by the reduction in the IFN-c expression. In general, IAV replicates in epithelial cells [26] as well as in immune cells like macrophages [52,53], which results in the release of numerous potent immune mediators. For example, IFN-a/b and IL-18 were secreted from IAV-infected macrophages and caused thereby an activation of natural killer (NK) cells and T-lymphocytes, which leads to IFN-c release [54].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are produced locally and systemically in animals during influenza infection [87][88][89], and the occurrence of the cytokine storm "hypercytokinemia" has been proposed to contribute to the increased severity of diseases caused by the highly pathogenic viruses [90][91][92]. In addition, antagonism of TNF-a, IL-1a, and IL-6 has been found to partly prevent the decrease in feeding and loss of body weight of mice induced by influenza virus infection [93].…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
“…The protective mechanism was therefore suggested to be the induction of IFN-g in T cells [57]. In a more recent study, the immune responses induced by glycyrrhizin may result in the loss of control of viral replication by cytotoxic immune cells, including NK cells and CD8 þ T lymphocytes [92].…”
Section: Immune-enhancing Activitiesmentioning
confidence: 99%
See 1 more Smart Citation